(untitled) (Ameghiniana, 2015)
Actinocythereis imbeensis n. sp. is described from the early Miocene strata of the Pelotas Basin, the southernmost Brazilian marginal basin. The specimens were recovered from the base to the top of an offshore core composed of greenish-gray shale interpreted as part of a transgressive sequence. Morphological features and faunal composition indicate that the ostracods were autochthonous and lived in the photic zone. Resumen. UNA NUEVA ESPECIE DE TRACHYLEBERIDIDAE (OSTRACODA, CRUSTACEA) DEL MIOCENO DE LA CUENCA DE PELOTAS, EXTREMO SUR DE BRASIL. Se describe Actinocythereis imbeensis n. sp., del Mioceno inferior de la cuenca marginal de Pelotas de Brasil meridional. Los especímenes fueron recuperados a lo largo de un testigo marino litológicamente constituido por lutita gris verdosa interpretada como parte de una secuencia transgresiva. Las características morfológicas y la composición faunística de los ostrácodos indican un conjunto autóctono viviendo en la zona fótica.